PEMBERDAYAAN KELUARGA MELALUI BISNIS ONLINE SHOP DI DESA JONJO KECAMATAN PARIGI KABUPATEN GOWA - Rismawati, Rismawati; Syamsidar, Syamsidar; Shahib, Muzdalifah (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2021)
This research aims to determine (1) studying of obstacles in empowering families through an online shop business in Jonjo Village, Parigi District, Gowa Regency (2) studying of family empowerment efforts through an online shop business in Jonjo Village, Parigi District, Gowa Regency. This type of research is a qualitative research that uses descriptive analysis method where the methodology of this research is through a sociological approach through various series. Such as observation, interviews and documentation. And supported by primary data sources and secondary data. The results of this study are obstacles in empowering families through online shop businesses including the weak internet network, the absence of assistance from the government or local institutions, capital and selling prices, trust problems or the suitability of buyer expectations for online shop businesses, the number of competitors with the same business. the number of scams on social media, financial management problems, diverse buyer character, and late delivery. Every obstacle must have a way out, just like in an online shop business, online shop businessmen must look for efforts to deal with existing obstacles, including getting up early the network is smoother, learning from social media, providing examples of goods being sold, promotions on social media, resellers ( retailers), business people as consumers of merchandise,online shop bussines financial bookkeeping, shipping agreements.